Incompatible Aedes aegypti male releases as an intervention to reduce mosquito population-A field trial in Puerto Rico. - Liliana Sánchez-González; Jacob E Crawford; Laura E Adams; Grayson Brown; Kyle R Ryff; Mark Delorey; Jose Ruiz-Valcarcel; Nicole Nazario; Nexilianne Borrero; Julieanne Miranda; Sara N Mitchell; Paul I Howell; et al. (PLoS Neglected Tropical Diseases)
Mosquito-transmitted viruses such as dengue are a global and growing public health challenge. Without widely available vaccines, mosquito control is the primary tool for fighting the spread of these viruses. New mosquito control technologies are needed to complement existing methods, given current challenges with scalability, acceptability, and effectiveness. A field trial was conducted in collaboration with the Communities Organized to Prevent Arboviruses project in Ponce, Puerto Rico, to measure entomological and epidemiological effects of reducing Aedes aegypti populations using Wolbachia incompatible insect technique. We packed and shipped Wolbachia-males from California and released them into 19 treatment clusters from September 2020 to December 2020. Preliminary evaluation revealed sub-optimal Wolbachia-male densities and impact on the wild-type population. In 2021, we shifted to a phased release strategy starting in four clusters, reducing the mosquito population by 49% (CI 29-63%). We describe the investigation into male quality and other factors that may have limited the impact of Wolbachia-male releases. Laboratory assays showed a small but significant impact of packing and shipping on male fitness. However, mark-release-recapture assessments suggest that male daily survival rates in the field may have been significantly impacted. We compared induced-sterility levels and suppression of the wild population and found patterns consistent with mosquito population compensation in response to our intervention. Analysis of epidemiological impact was not possible due to very low viral transmission rates during the intervention period. Our entomological impact data provide evidence that Wolbachia incompatible-male releases reduced Ae. aegypti populations, although efficacy will be maximized when releases are part of an integrated control program. With improvement of shipping vessels and shipped male fitness, packing and shipping male mosquitoes could provide a key solution for expanding access to this technology. Our project underscores the challenges involved in large and complex field effectiveness assessments of novel vector control methods.